S98 Pellino-1 regulates the responses of the airway to viral infection. (December 2018) - Marsh, EK; Prestwich, EC; Marriott, HM; Williams, L; Hart, AR; Muir, CF; Parker, LC; Jonker, MR; Heijink, IH; Timens, W; Fife, M; Hussell, T; et al.
Abstract : Introduction and objectives: Exposure to respiratory pathogens is a leading cause of exacerbations of airway diseases such as asthma and chronic obstructive pulmonary disease (COPD). We have shown that Pellino-1, an E3 ubiquitin ligase, is involved in viral-induced TLR3 signalling; thus we sought to describe the role of Pellino-1 in the host response to viral stimulation of the airway. Methods: Pellino-1 expression was examined in bronchial sections from patients with GOLD stage 2 COPD (n=7) and healthy controls (n=8). Primary bronchial epithelial cells (PBECs, n=5) in which Pellino-1 expression had been knocked down using siRNA, were extracellularly challenged with the TLR3 agonist poly(I:C). C57BL/6 Peli1 -/- mice and wild type littermates were subjected to intranasal infection with the clinically-relevant respiratory viruses rhinovirus (RV1B) and influenza A, and responses monitored up to 8 days later. Results: We show that Pellino-1 is expressed in the airways of normal subjects and those with COPD. In the absence of Pellino-1, PBECs showed significant reduction in proinflammatory cytokines, including CXCL8 and IL-6, upon TLR3 activation. Surprisingly however, knockout of Peli1 in the murine lung resulted in increased production of the proinflammatory cytokines IL-6 and TNFα with viral infection. This was accompanied by an enhanced recruitment of immune cells to the airways in these animals, including a population of innate B cells, without loss of viral replication. Conclusions: We conclude that Pellino-1 functions as a positive regulator for antiviral responses in isolated bronchial epithelial cells and in systemic responses to TLR3 activation, but it has the opposite effect in the lung. Here, Pellino-1 has a distinct function in the down-regulation of antiviral inflammation; a role dissociated from viral replication. Our data therefore suggest that Pellino-1 may offer therapeutic potential to limit viral inflammation in COPD and asthma.